A Preliminary Report on Prehistoric Investigation in the Middle Ong River Basin with Particular Reference to the Uttali and the Ghensali Stream, Southern Bargarh Upland, Odisha. (1st July 2021) - Barik, Kshirasindhu; Sabale, P. D.
The paper presents a preliminary report on the systematic surface exploration conducted in the Middle Ong basin with particular focus on the northern tributaries, viz. the Uttali, Ghensali and Mongragod stream in the southern Bargarh Upland of Western Odisha. The investigations have resulted in the discovery of 43 new prehistoric sites in the area with predominance of microlithic components. These sites are observed in different geomorphological contexts, such as, in the cliff surface of riverbanks, hillslope, foothills and rocky outcrops. Abundant availability of raw materials, mainly chert of different colors and vein quartz in the area seem to have attracted the prehistoric communities for intensive settlements in the area. while sporadic acheulian artifacts have been found scattered here and there, most of the documented sites are dominated by microlithic components, some of which have also been associated with used/unused red ochre minerals, suggesting advanced cognitive abilities and symbolic behavior of the microlith using communities in the area of investigation.